Politics, theology, and history - Plant, Raymond (Cambridge studies in ideology and religion., 2001)
Lord Plant focuses on the role that religious belief can and ought to play in argument about public policy in a pluralistic society. He examines the potential political implications of Christian belief and the ways in which it may be deployed in political debate. The book discusses the place of religious belief in the formation of policy and asks what issues in modern society might be the legitimate objects of a Christian social and political concern.